Green Approaches Involving Liquid Phase Microextraction, Monolithic Column And Capacitively Coupled Contactless Conductivity Detection In Flow Techniques - Makahleh, Ahmad (Moh’d Ali) Hasan (2011)
This thesis deals with the developments of new analytical methods in flow techniques (high performance liquid chromatography (HPLC) and flow injection analysis). An important goal of these methods is the use of green approaches (solventless microextraction, monolithic column, capacitively coupled contactless conductivity detector (C4D), and automation) to achieve the respective objectives. A hollow fiber liquid phase microextraction technique was used as sample preparation for the extraction of trace amounts of rosiglitazone (anti-diabetic drug) in biological fluids.